Intraindividual Specificity and Stability of Human EEG: Comparing a Linear vs a Nonlinear Approach - Dünki, R. M.; Schmid, G. B.; Stassen, H. H. (Methods of Information in Medicine, 2000)
We have applied the so-called “unfolding dimension approach’’ to reanalyze an earlier longitudinal EEG study. Both linear and nonlinear approaches show that the EEG comprises a static, person-specific part upon which nonstatic and state-specific parts are superimposed. The intraindivi-dual specificity and stability of the genetic part are similar between methods. This is assessed by comparing the outcome of a person to his own outcomes at later times (14 days and 5 years later). The nonlinear method revealed a median correlation coefficient = 0.55, whereas advanced linear methods showed a median = 0.84. An apparent effect for the 5-year interval was detected with the nonlinear method and is discussed in terms of the different assumptions of the two approaches concerning EEG signal generation.
Keywords: Dimension Analysis; Similarity Approach; EEG Stability; Power Spectrum